AVENUE21. Automatisierter und vernetzter Verkehr: Entwicklungen des urbanen Europa - Mitteregger, Mathias (TU Wien Academic Press, 2020)
The following publication shows the results of a Daimler and Benz Foundation grant-supported research project at the TU Wien. It is the shared achievement of the Faculty of Architecture and Planning and comprises more than two and a half years of interdisciplinary teamwork. The subject of the study are the effects of automated and connected vehicles on the European city, and the pre-conditions under which this technology can make a positive impact on urban development. The research team advocate for two theses which have received little notice in scientific discussions: • Automated and connected vehicles will not gain acceptance in all subspaces of the city for a long time. As a result, the assumed impact - from transport safety to efficiency, as well as spatial effects - must be newly appraised. • To ensure that this technology makes a positive contribution to the mobility of the future, transportation regulations and settlement policies must continue to develop, as well. Established territorial, institutional and organisational borders should be questioned, and soon. Despite, or perhaps because of current insecurity, we find ourselves at the start of a phase of creation and experimentation for the development of new technology, but also for politics, urban planning, administrations and the civilian community.